Comparison of seismic fragility of RC moment-resisting frame structures designed according to Chinese and Indian code. (April 2023) - Biva, Gyawali; Huanjun, Jiang
Highlights: Seismic fragility analysis of RC moment-resisting frame structures designed as per Chinese and Indian code is conducted. Parametric study is conducted by varying the height of the building and the type of foundation soil. Response of the structure is obtained through non-linear time history analysis. Structure designed as per Chinese code is safer than structure designed as per Indian code for same earthquake level. Abstract: Seismic fragility analysis is a method used to evaluate the vulnerability experienced by structures when subjected to earthquakes. In this study, the seismic performance of 18 reinforced concrete moment-resisting frame structures designed according to Chinese code and Indian code is analyzed. A parametric study is conducted by varying the height of the building and the type of soil on which the building is constructed. Nonlinear time history analyses are conducted to develop fragility curves for four different damage levels: fully operational, operational, repairable, and collapse prevention. Linear regression analysis is conducted to correlate the engineering demand parameter (maximum inter-story drift) and the intensity of an earthquake (peak ground acceleration). The results show that the structures designed according to the Indian code experience higher story drift than those designed according to Chinese code, making them more vulnerable to the same earthquake intensity.